(untitled) (Research, Society and Development, 2020)
Objective: we sought to apprehend the social representations of the Primary Health Care teams about the care practices for women in situations of domestic violence. Method: qualitative research based on the Theory of Social Representations. The data were collected through semi-structured interviews applied to 24 professionals of Primary Health Care who work in the Family Health Strategy of a city in the interior of Bahia. For data analysis, the software Interface de R pour les Multidimensionnelles de Textes et de Questionnaires was used from the perspective of Factor Analysis by Correspondence and thematic content analysis technique to contextualize the results. Results: care practices emerged related to listening, encouraging, empowering and reporting cases. It was also evident, the professionals’ fear of possible reprisals caused by the aggressors and the lack of communication between the sectors of the network to confront domestic violence against women. The support of family members, neighbors, health professionals and public sectors is pointed out as an important care practice for women to get out of situations of violence. Conclusion: there is an urgent need to review the professional training process, promote the training and protection of health professionals for the best development of care practices for women in situations of domestic violence.